2020
DOI: 10.3389/fcell.2020.573859
|View full text |Cite
|
Sign up to set email alerts
|

Transgelins: Cytoskeletal Associated Proteins Implicated in the Metastasis of Colorectal Cancer

Abstract: Transgelins, including transgelin-1 (T-1), transgelin-2 (T-2), and transgelin-3 (T-3), are a family of actin-binding proteins (ABPs) that can alter the structure and morphology of the cytoskeleton. These proteins function by regulating migration, proliferation and apoptosis in many different cancers. Several studies have shown that in various types of tumor cells, including colorectal cancer (CRC) cells, and in the tumor microenvironment, the expression and biological effects of transgelins are diverse and may… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
17
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 95 publications
(104 reference statements)
2
17
0
Order By: Relevance
“…The calponin family proteins (Figure 1a) including calponin, transgelin (also known as SM22, NP25, Mp20, or myophilin), and UNC-87, bind to actin filaments and regulate actin filament stability and actomyosin contractility (Assinder, Stanton, & Prasad, 2009;Carmichael, Winder, Walsh, & Kargacin, 1994;Dvorakova, Nenutil, & Bouchal, 2014;Liu, Zhang, Li, & Wang, 2020;Rozenblum & Gimona, 2008;Winder & Walsh, 1996). Calponin was originally isolated from chicken gizzard smooth muscle as a candidate regulator of contraction with a troponin-like function (Takahashi, Hiwada, & Kokubu, 1986;Takahashi, Hiwada, & Kokubu, 1988).…”
Section: The Calponin Family Proteins Regulate Actin Filament Stability and Actomyosin Contractilitymentioning
confidence: 99%
See 2 more Smart Citations
“…The calponin family proteins (Figure 1a) including calponin, transgelin (also known as SM22, NP25, Mp20, or myophilin), and UNC-87, bind to actin filaments and regulate actin filament stability and actomyosin contractility (Assinder, Stanton, & Prasad, 2009;Carmichael, Winder, Walsh, & Kargacin, 1994;Dvorakova, Nenutil, & Bouchal, 2014;Liu, Zhang, Li, & Wang, 2020;Rozenblum & Gimona, 2008;Winder & Walsh, 1996). Calponin was originally isolated from chicken gizzard smooth muscle as a candidate regulator of contraction with a troponin-like function (Takahashi, Hiwada, & Kokubu, 1986;Takahashi, Hiwada, & Kokubu, 1988).…”
Section: The Calponin Family Proteins Regulate Actin Filament Stability and Actomyosin Contractilitymentioning
confidence: 99%
“…The interpretation of the phenotypes is complicated by the presence of multiple calponin isoforms and calponin-related proteins, which may have overlapping roles in muscle contractility. Mammals have three calponin genes (CNN1, CNN2, and CNN3) (Liu & Jin, 2016) and three transgelin genes (TAGLN, TAGLN2, and TAGLN3) (Liu et al, 2020). Calponin-2 (CNN2) is also expressed in smooth muscle (Hossain, Hwang, Huang, Sasaki, & Jin, 2003), but either single deletion of CNN2 or double deletion of CNN1 and CNN2 in mice still causes only modest alterations in smooth muscle contractility (Feng, Wang, Takahashi, & Jin, 2019).…”
Section: The Calponin Family Proteins Regulate Actin Filament Stability and Actomyosin Contractilitymentioning
confidence: 99%
See 1 more Smart Citation
“…Transgelins encompass an actin-binding protein family, well-conserved from yeast to human, implicated in cytoskeleton remodeling (Shapland et al, 1988;Assinder et al, 2009;Liu et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Transgelins encompass an actin-binding protein family, well-conserved from yeast to human, implicated in cytoskeleton remodeling ( Shapland et al, 1988 ; Assinder et al, 2009 ; Liu et al, 2020 ). Transgelin’s name was coined by its ability to induce actin gelation in vitro ( Shapland et al, 1993 ), while subsequent studies revealed actin filament bundling activity and its role in cellular contractility ( Han et al, 2009 ).…”
Section: Introductionmentioning
confidence: 99%